Amphipod size variation and substrate color preferences in coastal habitats: An experimental study in Ujung Genteng, West Java - Krisanti Majariana; Mashar Ali; Puspa Ayu Inna; Farajallah Achmad; Ananingtyas; Aprilia Mita; Zainal Arifin Jauhar; Zulmi Reza; Eko Susilo Vendi; Aulia Putri Tazkiah; Iskandar Irwan; Musti’atin; et al. (BIO Web of Conferences)
Amphipods are key detritivores in coastal ecosystems, and their behaviour and habitat selection can offer insights into their survival strategies. This study aims to investigate the substrate colour preferences and size variation in Traskorchestia georgiana, an amphipod species inhabiting sandy beaches. Experiment was done in August 2024 at coastal habitat of Ujung Genteng, Sukabumi, West java. Through a series of controlled experiments, amphipods were exposed to four different substrate colours (yellow, pink, green, and light blue) to assess their preferences and size distribution with Kruskal-Wallis and Friedman Test. Although statistical analysis indicated no significant colour preferences (p > 0.05), observable trends suggested a higher average number of amphipods on the pink substrate compared to the light blue. Additionally, size variation among the amphipods did not correlate with substrate colour. These findings suggest that other factors, such as substrate texture or moisture content, may play a more important role in habitat selection for these species. The study contributes to a broader understanding of amphipod behavior and provides insights into coastal ecosystem management and conservation, particularly in the context of habitat restoration efforts.